2020
DOI: 10.1007/s13744-020-00813-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Spatial Distribution of Boll Weevil in Commercial Cotton Fields

Abstract: The departure and arrival of boll weevil in cotton fields have fostered major control decisions against this pest over time. Field colonization and distribution of boll weevil were evaluated using cotton fields from 93.7 to 154 ha each, located in Serra da Petrovina and Campo Verde, both in the Cerrado biome of Mato Grosso State, Brazil, as a function of cotton field bordering vegetation and crop phenology. The monitoring of adult weevils was carried out using traps containing sex and aggregation pheromone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous research on adult boll weevil in-field distributions used whole-plant sampling 14 and pheromone-based traps both possessing different dimensions for analyzing dispersion compared with the current approach. 8,15,41 Alternatively, application of kriging and other techniques to characterize in-field cotton pest distributions were used to describe spatial distribution of pests such as the pink bollworm, 42 cotton bollworm, 43,44 pentatomid stink bugs [45][46][47][48] and thrips. 49 Our study is the first to describe spatial distribution of the boll weevil with ordinary kriging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on adult boll weevil in-field distributions used whole-plant sampling 14 and pheromone-based traps both possessing different dimensions for analyzing dispersion compared with the current approach. 8,15,41 Alternatively, application of kriging and other techniques to characterize in-field cotton pest distributions were used to describe spatial distribution of pests such as the pink bollworm, 42 cotton bollworm, 43,44 pentatomid stink bugs [45][46][47][48] and thrips. 49 Our study is the first to describe spatial distribution of the boll weevil with ordinary kriging.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,13 The spatial distribution of boll weevils has been investigated using mean-variance relationships 4,14 without considering within-field spatial density distribution, or has been based on pheromone-baited trap captures. 15 The most accurate approach is the use of geostatistics because the position of the samples in space is accounted for. 16 Recent work reported that geostatistics is of particular interest for pest management because it allows inferences about the minimum inter-sample distance needed to obtain independent estimations and indicates patterns of distribution and colonization of an organism, all of which are crucial for the development of effective sampling programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation supports the hypothesis that resistance selection in the past should be of a low order, considering that boll weevil would be exposed to insecticides only during the cotton season, with most individuals exposed to cotton pesticides likely dying before the next cotton cropping season. However, this hypothesis has been changed recently due to the observed presence of boll weevils in volunteer cotton plants developing in soybean and corn fields 14,51 . This occurrence of volunteer cotton appears to be due to the use of herbicide‐resistant cotton (Roundup Ready cotton), as these plants can survive the herbicide roundup® commonly used in these others 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as soon as cotton plants are available for infestation again, dispersing adults will reinfest the plants from the refuge areas [32] or from surviving individuals in the area [33]. The existence of extensively cultivated areas established in large planting date windows may favor population build-up across the fields [34,35]. Therefore, planting dates can have an impact on pest outbreaks.…”
Section: Introductionmentioning
confidence: 99%